Tumor-associated macrophages correlate with better outcome in SHH medulloblastoma - Zhang, Jin; Li, Shuting; Wang, Yuan; Liu, Jingjing; Liu, Yan; Gong, Xiaojun; Sun, Yanling; Sun, Liming; Li, Zhigang; Wang, Tianyou; Du, Shuxu; Wu, Wanshui (Frontiers in Oncology, 2025)
ObjectiveTumor-associated macrophages (TAMs) constitute a significant proportion of the immune cell population within brain tumors. The polarization of macrophages exerts an important influence on the tumor microenvironment (TME). Nevertheless, the specific role of TAMs in sonic hedgehog (SHH) medulloblastoma remains unclear. To investigate the polarization characteristics and effects of TAMs in SHH medulloblastoma, we evaluated the infiltration of M1 and M2 macrophages in SHH medulloblastoma tissues and analyzed the correlation between TAMs recruitment and the clinical outcome of SHH medulloblastoma patients.MethodsWe enrolled a total of 42 patients diagnosed with SHH medulloblastoma. Using multiple immunofluorescence staining on paraffin-embedded sections, we detected the activated phenotype (M1/M2) by monoclonal antibodies for CD68, HLA-DR and CD163. Subsequently, we analyzed the correlation between TAMs and clinical characteristics as well as prognostic factors.ResultsThe median age of 42 patients (31 boys, 11 girls) was 5.3 years (range: 0.8-15.1 years). All patients had confirmed pathological types, including 4 cases of classic medulloblastoma (CMB), 33 cases of desmoplastic/nodular medulloblastoma (DNMB), 3 cases of medulloblastoma with extensive nodularity (MBEN), and 2 cases of large-cell/anaplastic medulloblastoma (LCA). Thirteen cases presented with metastasis at diagnosis, while twenty-nine cases were without metastasis. Four cases had high-risk genetic abnormalities. Different proportions of macrophages were found in the collected medulloblastoma tissues, and large amounts of CD68+HLA-DR+CD163+ cells were found. The study revealed that Mtotal (total macrophages) and Mmix (CD68+HLA-DR+CD163+ cells) were significantly higher in group of patients <5 years old (P < 0.05), and Mtotal in non-metastatic group were significantly higher than that in metastatic group (P = 0.043). M2 macrophages in CMB group were significantly higher than that in DNMB/MBEN group (P = 0.036), M1 macrophages were significantly higher in children without high-risk genetic abnormalities (P = 0.007). Five-year PFS was significantly poorer in patients ≥5 years old and metastatic group (P < 0.05). High Mtotal group had a better 5-year PFS (P = 0.000), whereas high M2 group had both better 5-year PFS and OS (P = 0.001, P = 0.001). Multivariate analysis showed that Mtotal and M2 macrophages were independent prognostic factors for 5-year PFS, and M2 macrophages were an independent prognostic factor for 5-year OS.ConclusionThe increase in total macrophages and M2 macrophages predicts a better outcome of SHH medulloblastoma. TAMs especially M2 macrophages might be a therapeutic target for SHH medulloblastoma.